Optimum watermark detection of ultrasonic echo medical images - Khawne, Amnach; Attachoo, Boonwat; Hamamoto, Kazuhiko (My University, 2015)
To prevent unauthorized access to a person's medical images, it is widely acknowledged that the security features of confidentiality, availability and integrity should be in place. This paper proposes the watermarking of ultrasonic echo images together with optimal watermark detection, in which pseudorandom noise is added to the images for integrity. The optimum watermark detection is the integration of the generalized Gaussian distribution (ρ-GGD) and the Cauchy distribution. The results show that the proposed method gives good detection performance. The proposed method not merely achieves optimum detection using the Rao test but also leads to the highest detection probability with JPEG2000 compression. Compared with other detection methods, our proposed method exhibits better watermark detection performance even when the watermark-to-document ratio (WDR) is -50 dB.
Keywords: Cauchy distribution; Generalized gaussian distribution; Image watermarking; Optimum detection